The patchwork pocket palette a handy visual guide to mixing and matching colored fabrics - Walker, Anne (San Francisco, CA Chronicle Books, 1995)
D., 8/99
Keywords: Patchwork--Patterns; Quilting--Patterns; Color in textile crafts